1979
DOI: 10.3109/00016487909126405
|View full text |Cite
|
Sign up to set email alerts
|

Indications And Results of the Multichannel Cochlear Implant

Abstract: In the case of total deafness, the multichannel cochlear implant prosthesis constitutes a substantial improvement. It allows known words to be recognized without lip reading, with a great percentage of good responses. Clinical and phoniatric results are reported in 21 cases of patients with implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…The choice of this strategy was justified on the basis of psychophysical results. These results {Simmons, 1966; House, 1976; Eddington et al, 1978;Burian et al, 1979;Pialoux et al, 1979;andTong et al, 1979, 1982) showed that pitch, sharpness, and spectral color produced by activating different intracochlear electrodes in postlingually' deaf patients were found to vary in accordance with the tonotopic organization of the cochlea, although this tonotopic orderliness was not apparent in prelingually deaf patients {for example, subject JB reported in Eddington et al, 1978). Pitch was also found to increase with electric pulse rate and loudness with current level.…”
Section: Recent Studies From Various Research Centers Havementioning
confidence: 59%
“…The choice of this strategy was justified on the basis of psychophysical results. These results {Simmons, 1966; House, 1976; Eddington et al, 1978;Burian et al, 1979;Pialoux et al, 1979;andTong et al, 1979, 1982) showed that pitch, sharpness, and spectral color produced by activating different intracochlear electrodes in postlingually' deaf patients were found to vary in accordance with the tonotopic organization of the cochlea, although this tonotopic orderliness was not apparent in prelingually deaf patients {for example, subject JB reported in Eddington et al, 1978). Pitch was also found to increase with electric pulse rate and loudness with current level.…”
Section: Recent Studies From Various Research Centers Havementioning
confidence: 59%
“…Intra-cochlear multiple-channel electrical stimulation has recently been used by a number of research centers as a means of helping to alleviate profound or total hearing loss (Simmons et al, 1979a;House, 1976;Ed-, dington et al, 1978;Burian et al , 1979;Pialoux et al , 1979;Merzenieh et al, 1979). In selecting a speech processing strategy that will restore useful hearing in patients, it is important to examine the nature of the hearing sensations produced by multiple-channel electrical stimulation.…”
Section: Introductionmentioning
confidence: 96%
“…Even though the early devices stimulated the auditory nerve with one electrode only, some lucky patients managed to hear again and even understand speech. Nowadays, it is technologically possible to use more than one electrode, in order to stimulate more of the thousands of neurons the auditory nerve is made of [33,9]. However, the more electrodes, the more parameters to tune.…”
Section: Cochlear Implantsmentioning
confidence: 99%